Pengaruh Penggunaan Kompos Pelepah Kelapa Sawit dengan Berbagai Mikroorganisme Lokal (MoL) dan Cara Aplikasinya terhadap Sifat Fisik Tanah dan Produksi Tembakau (Nicotiana tabacum L.) - Aviv Event Adviadri Sinaga; Rijadi Subiantoro; Fatahillah Fatahillah (Politeknik Negeri Lampung, 2015)
Organic fertilizer has the advantage of containing nutrients more complete than the inorganic fertilizer albeit in relatively small quantities. In general, organic fertilizers may contribute to improve the physical, chemical, and biological soil. Peneltian purpose compost To determine the effect of palm fronds on the physical properties of the soil (moisture content, bulk density and porosity of the soil) and dry weight of leaf tobacco. The experiment was conducted in September 2015 in State Polytechnic of Lampung experimental Â garden, arranged in a randomized block design factorial with bio-activator treatment differences in the way applications compost mixed with soil and on the ground. Soil sampling was take 5 cm above ground. Observations carried out on soil water content, bulk density, porosity of the soil and leaf dry weight. The results showed that compost of oil palm fronds affect the physical properties of the soil, but not significantly different to the dry weight of leaf tobacco.Keywords: compost, soil physical properties, tobaccoPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/15